Pengaruh Model Pembelajaran Discovery Learning Terhadap Motivasi Belajar Siswa Pada Pembelajaran PAI Di UPTD SMP Negeri 5 Kecamatan Pangkalan Koto Baru - Annisa Zahrahul Jannah; Supriadi Supriadi; Arifmiboy Arifmiboy; Darul Ilmi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Thistresearrch is motivatedubyothe condition ofjstudents' motivation toistudy PAI which is still relatively low, so that when learning many students are less active. Theipurposeoof thisustudy wasito findiyoutr howtmuchuinfluenceuthe observational learning model hadoion students' learning motivation in PAI learning at UPTD SMP Negeri 5Kecamatan Pangkalan Koto Baru.Thiis researchtisua Quasi Experimentail Designiresearch, with a tendency of quantitative data. The data analysiis technique ues the Normality Test with the Kolmogrov Smirnov formula, and the homogeneityytesttwith Fisher's test followed by hypothesis testing with Independent t-test. Basedron the test results and discussion of the research data, the results of the t test. The exerimental class motivation obtained an average of 155.47 and in the control class obtained an averag of 140.50. Itccan beeconcluded thaat the effect ofuusing the discoverry learing mdl on student learing motivation in PAI learning at UPTD SMP Negeri 5 Kecamatan Pangkalan Koto Baru is strong, as evidenced by the number 155.47 > 140.50, then H0 is rejected and H1 is acepted.